Linear dichroism infrared resonance in overdoped, underdoped, and optimally doped cuprate superconductors - Mukherjee, A.; Seo, J.; Arik, M. M.; Zhang, H.; Zhang, C. C.; Kirzhner, T.; George, D. K.; Markelz, A. G.; Armitage, N. P.; Koren, G.; Wei, J. Y. T.; Cerne, J. (Physical Review B, 2020)
By measuring the polarization changes in terahertz, infrared, and visible radiation over an extended energy range (3-2330 meV), we observe symmetry breaking in cuprate high-temperature superconductors over wide energy, doping, and temperature ranges. We measure the polarization rotation (Re[theta(F)]) and ellipticity (Im[theta(F)]) of transmitted radiation through thin films as the sample is rotated. We observe a twofold rotational symmetry in theta(F), which is associated with linear dichroism (LD) and occurs when electromagnetic radiation polarized along one direction is absorbed more strongly than radiation polarized in the perpendicular direction. Such polarization anisotropies can be generally associated with symmetry breakings. We measure the amplitude of the LD signal and study its temperature, energy, and doping dependence. The LD signal shows a resonant behavior with a peak in the few hundred meV range, which is coincident with the midinfrared optical feature that has been associated with the formation of the pseudogap state. The strongest LD signal is found in underdoped films, although it is also observed in optimally and overdoped samples. The LD signal is consistent with an electronic nematic order which is decoupled from the crystallographic axes as well as novel magnetoelectric effects.
ISI Document Delivery No.: NE5GO Times Cited: 0 Cited Reference Count: 30 Cited References: Acbas G, 2009, PHYS REV LETT, V103, DOI 10.1103/PhysRevLett.103.137201 Armitage NP, 2014, PHYS REV B, V90, DOI 10.1103/PhysRevB.90.035135 Arpaia R, 2018, PHY REV MATER, V2, DOI 10.1103/PhysRevMaterials.2.024804 Basov DN, 2005, REV MOD PHYS, V77, P721, DOI 10.1103/RevModPhys.77.721 Blumberg G, 1996, PHYS REV B, V53, P11930, DOI 10.1103/PhysRevB.53.R11930 Cerne J, 2000, PHYS REV LETT, V84, P3418, DOI 10.1103/PhysRevLett.84.3418 Fauque B, 2006, PHYS REV LETT, V96, DOI 10.1103/PhysRevLett.96.197001 Fridman I, 2011, PHYS REV B, V84, DOI 10.1103/PhysRevB.84.104522 George DK, 2012, J OPT SOC AM B, V29, P1406, DOI 10.1364/JOSAB.29.001406 Halperin B. I., 1991, SPRINGER P PHYS, V60, P439 Humlicek J, 2000, PHYS REV B, V61, P14554, DOI 10.1103/PhysRevB.61.14554 KOREN G, 1989, APPL PHYS LETT, V54, P1054, DOI 10.1063/1.101559 Koren G, 2016, PHYS REV B, V94, DOI 10.1103/PhysRevB.94.174515 Lubashevsky Y, 2014, PHYS REV LETT, V112, DOI 10.1103/PhysRevLett.112.147001 Mukherjee A, 2019, PHYS REV B, V99, DOI 10.1103/PhysRevB.99.085440 Nie LM, 2014, P NATL ACAD SCI USA, V111, P7980, DOI 10.1073/pnas.1406019111 Orenstein J, 2011, PHYS REV LETT, V107, DOI 10.1103/PhysRevLett.107.067002 PISAREV RV, 1991, PHASE TRANSIT, V37, P63, DOI 10.1080/01411599108203448 Simon ME, 2002, PHYS REV LETT, V89, DOI 10.1103/PhysRevLett.89.247003 TROFIMOV IE, 1994, APPL PHYS LETT, V65, P2481, DOI 10.1063/1.112671 Varma CM, 2014, EPL-EUROPHYS LETT, V106, DOI 10.1209/0295-5075/106/27001 Varma CM, 1997, PHYS REV B, V55, P14554, DOI 10.1103/PhysRevB.55.14554 Wu J, 2017, NATURE, V547, P432, DOI 10.1038/nature23290 Xia J, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.127002 Yakes MK, 2010, NANO LETT, V10, P1559, DOI 10.1021/nl9035302 Yakovenko VM, 2015, PHYSICA B, V460, P159, DOI 10.1016/j.physb.2014.11.060 Zhang H, 2018, PHYS REV MATER, V2, DOI 10.1103/PhysRevMaterials.2.033803 Zhang J, 2018, SCI ADV, V4, DOI 10.1126/sciadv.aao5235 Zhao L, 2017, NAT PHYS, V13, P250, DOI [10.1038/nphys3962, 10.1038/NPHYS3962] Zhao L., 2018, ENCY MODERN OPTICS, P207 Mukherjee, A. Seo, J. Arik, M. M. Zhang, H. Zhang, C. C. Kirzhner, T. George, D. K. Markelz, A. G. Armitage, N. P. Koren, G. Wei, J. Y. T. Cerne, J. NSF-DMR GrantNational Science Foundation (NSF) [1410599]; NSFNational Science Foundation (NSF) [MCB 1616529, DMR 1905519]; DOEUnited States Department of Energy (DOE) [DE-SC0016317]; NSERCNatural Sciences and Engineering Research Council of Canada (NSERC); CFI-OITCanada Foundation for Innovation; Canadian Institute for Advanced ResearchCanadian Institute for Advanced Research (CIFAR) We are indebted to D. Hsieh, S. A. Kivelson, C. M. Varma, and L. Zhao for helpful discussions. We gratefully acknowledge support from NSF-DMR Grant No. 1410599 (J.C.). A.G.M. and D.K.G. were supported by NSF Grant No. MCB 1616529 and DOE Grant No. DE-SC0016317. Work in Toronto was supported by NSERC, CFI-OIT, and the Canadian Institute for Advanced Research. J.Y.T.W. thanks Kejun Xu for laboratory assistance in Toronto. N.P.A. was supported by NSF Grant No. DMR 1905519. 9 Amer physical soc College pk 2469-9969
Keywords: Materials Science; Physics

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
ISI Document Delivery No.: EI0HL Times Cited: 541 Cited Reference Count: 209 Cited References: Adam AJL, 2011, J INFRARED MILLIM TE, V32, P976, DOI 10.1007/s10762-011-9809-2 Ahmed SS, 2012, IEEE MICROW MAG, V13, P26, DOI 10.1109/MMM.2012.2205772 Alliance N., 2015, CISC VIS NETW IND GL, P1 [Anonymous], 2013, 178512012 IEEE [Anonymous], 2014, IEEE T ELECT DEVICES, V61 [Anonymous], 2012, 178522016 IEEE [Anonymous], 2015, P17852 IEEE Appleby R, 2015, P SOC PHOTO-OPT INS, V9462 Arnone DD, 1999, PROC SPIE, V3828, P209, DOI 10.1117/12.361037 Ashworth PC, 2009, OPT EXPRESS, V17, P12444, DOI 10.1364/OE.17.012444 AUSTON DH, 1988, IEEE J QUANTUM ELECT, V24, P184, DOI 10.1109/3.114 Barbieri S, 2011, NAT PHOTONICS, V5, P306, DOI [10.1038/NPHOTON.2011.49, 10.1038/nphoton.2011.49] Barker RJ., 2005, MODERN MICROWAVE MIL Basov DN, 2011, REV MOD PHYS, V83, P471, DOI 10.1103/RevModPhys.83.471 Bauwens M. F., 2014, P IEEEMTT S INT MICR, P1, DOI [10.1109/MWSYM.2014.68486 07, DOI 10.1109/MWSYM.2014.6848607] Beard MC, 2002, NANO LETT, V2, P983, DOI 10.1021/nl0256210 Beard MC, 2000, PHYS REV B, V62, P15764, DOI 10.1103/PhysRevB.62.15764 Bechtel HA, 2014, P NATL ACAD SCI USA, V111, P7191, DOI 10.1073/pnas.1400502111 Belkin MA, 2008, OPT EXPRESS, V16, P3242, DOI 10.1364/OE.16.003242 Belkin MA, 2015, PHYS SCRIPTA, V90, DOI 10.1088/0031-8949/90/11/118002 Bell R., 2012, INTRO FOURIER TRANSF Berry CW, 2013, NAT COMMUN, V4, DOI 10.1038/ncomms2638 Blanchard F, 2011, OPT EXPRESS, V19, P8277, DOI 10.1364/OE.19.008277 Blau J, 2013, P FREE EL LAS FEL 20, P486 Booske JH, 2011, IEEE T THZ SCI TECHN, V1, P54, DOI 10.1109/TTHZ.2011.2151610 Booske JH, 2008, PHYS PLASMAS, V15, DOI 10.1063/1.2838240 Boppel S, 2012, 2012 IEEE 12TH TOPICAL MEETING ON SILICON MONOLITHIC INTEGRATED CIRCUITS IN RF SYSTEMS (SIRF), P77, DOI 10.1109/SiRF.2012.6160142 Burghoff D, 2014, NAT PHOTONICS, V8, P462, DOI 10.1038/nphoton.2014.85 Busch SF, 2014, J INFRARED MILLIM TE, V35, P993, DOI 10.1007/s10762-014-0113-9 Byrne MB, 2011, APPL PHYS LETT, V98, DOI 10.1063/1.3579258 Carr GL, 2002, NATURE, V420, P153, DOI 10.1038/nature01175 Carranza IE, 2015, IEEE T THZ SCI TECHN, V5, P892, DOI 10.1109/TTHZ.2015.2463673 Castro-Camus E, 2007, OPT EXPRESS, V15, P7047, DOI 10.1364/OE.15.007047 Chan WL, 2007, REP PROG PHYS, V70, P1325, DOI 10.1088/0034-4885/70/8/R02 Chattopadhyay G, 2011, IEEE T THZ SCI TECHN, V1, P33, DOI 10.1109/TTHZ.2011.2159561 Chen HT, 2003, APPL PHYS LETT, V83, P3009, DOI 10.1063/1.1616668 Chen JN, 2012, NATURE, V487, P77, DOI 10.1038/nature11254 Cocker T L, 2016, J PHYS D, V16, P1421 Cocker TL, 2013, NAT PHOTONICS, V7, P620, DOI [10.1038/NPHOTON.2013.151, 10.1038/nphoton.2013.151] Coleman B, 2001, Issue Brief (Public Policy Inst (Am Assoc Retired Pers)), P1 Cooper KB, 2014, IEEE MICROW MAG, V15, P51, DOI 10.1109/MMM.2014.2356092 Cruz F C, 2007, C MICR OPT Cunningham J, 2010, ELECTRON LETT, V46, pS34, DOI 10.1049/el.2010.3317 Dean P, 2011, OPT LETT, V36, P2587, DOI 10.1364/OL.36.002587 Dietz RJB, 2014, OPT LETT, V39, P6482, DOI 10.1364/OL.39.006482 Dietz RJB, 2014, OPT EXPRESS, V22, P19411, DOI 10.1364/OE.22.019411 Dobrovolsky V, 2007, SEMICOND SCI TECH, V22, P103, DOI 10.1088/0268-1242/22/2/017 Ducournau G, 2014, IEEE T THZ SCI TECHN, V4, P328, DOI 10.1109/TTHZ.2014.2309006 Dunsmore J.P., 2012, HDB MICROWAVE COMPON Duvillaret L, 1999, APPL OPTICS, V38, P409, DOI 10.1364/AO.38.000409 Eisele M, 2014, NAT PHOTONICS, V8, P841, DOI [10.1038/nphoton.2014.225, 10.1038/NPHOTON.2014.225] Falconer RJ, 2012, J INFRARED MILLIM TE, V33, P973, DOI 10.1007/s10762-012-9915-9 Fathololoumi S, 2012, OPT EXPRESS, V20, P3866, DOI 10.1364/OE.20.003866 Fausti D, 2011, SCIENCE, V331, P189, DOI 10.1126/science.1197294 Federici J, 2010, J APPL PHYS, V107, DOI 10.1063/1.3386413 Fei Z, 2012, NATURE, V487, P82, DOI 10.1038/nature11253 FETTERMAN HR, 1974, APPL PHYS LETT, V24, P70, DOI 10.1063/1.1655098 Freeman JR, 2013, OPT EXPRESS, V21, P16162, DOI 10.1364/OE.21.016162 Frisk U, 2003, ASTRON ASTROPHYS, V402, pL27, DOI 10.1051/0004-6361:20030335 Garet F, 2014, APPL PHYS LETT, V105, DOI 10.1063/1.4890732 Gavrilov NG, 2007, NUCL INSTRUM METH A, V575, P54, DOI 10.1016/j.nima.2007.01.023 Gensch M., 2013, P 35 INT FREE EL LAS, P474 George DK, 2012, J OPT SOC AM B, V29, P1406, DOI 10.1364/JOSAB.29.001406 Giliberti V, 2013, APPL PHYS LETT, V103, DOI 10.1063/1.4819734 Grant J, 2013, LASER PHOTONICS REV, V7, P1043, DOI 10.1002/lpor.201300087 Green B, 2016, SCI REP-UK, V6, DOI 10.1038/srep22256 Griffith P.R., 2007, FOURIER TRANSFORM IN GRISCHKOWSKY D, 1990, J OPT SOC AM B, V7, P2006, DOI 10.1364/JOSAB.7.002006 Gruene P, 2008, SCIENCE, V321, P674, DOI 10.1126/science.1161166 Han NR, 2014, OPT LETT, V39, P3480, DOI 10.1364/OL.39.003480 Han RN, 2013, IEEE J SOLID-ST CIRC, V48, P2296, DOI 10.1109/JSSC.2013.2269856 Hanham SM, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4927242 Hassel J, 2015, PROC SPIE, V9651, DOI 10.1117/12.2197522 Hauri CP, 2011, APPL PHYS LETT, V99, DOI 10.1063/1.3655331 He W, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4932099 Hebling J, 2002, OPT EXPRESS, V10, P1161, DOI 10.1364/OE.10.001161 Heinz E, 2015, J INFRARED MILLIM TE, V36, P879, DOI 10.1007/s10762-015-0170-8 Henry SC, 2012, OPT ENG, V51, DOI 10.1117/1.OE.51.9.091603 Hesler J L, 2006, P 7 INT S SPAC TER T, P215 Hintzsche H, 2012, CRIT REV ENV SCI TEC, V42, P2408, DOI 10.1080/10643389.2011.574206 Hishida M, 2011, PHYS REV LETT, V106, DOI 10.1103/PhysRevLett.106.158102 Ho IC, 2010, OPT EXPRESS, V18, P2872, DOI 10.1364/OE.18.002872 HU BB, 1995, OPT LETT, V20, P1716, DOI 10.1364/OL.20.001716 Huang C, 2012, PHYS REV B, V85 Huber R, 2001, NATURE, V414, P286, DOI 10.1038/35104522 Jankowiak A., 2013, Synchrotron Radiation News, V26, P22, DOI 10.1080/08940886.2013.791212 Jepsen PU, 2007, CHEM PHYS LETT, V442, P275, DOI 10.1016/j.cplett.2007.05.112 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Jepsen PU, 2005, OPT LETT, V30, P29, DOI 10.1364/OL.30.000029 JUICE-Jupiter Icy Moons Explorer, 2014, SRE20141 JUICE EUR S, P1 Kallfass I, 2011, IEEE T THZ SCI TECHN, V1, P477, DOI 10.1109/TTHZ.2011.2160021 Kampfrath T, 2013, NAT PHOTONICS, V7, P680, DOI [10.1038/nphoton.2013.184, 10.1038/NPHOTON.2013.184] Kan T, 2015, NAT COMMUN, V6, DOI 10.1038/ncomms9422 Karpowicz N, 2008, APPL PHYS LETT, V92, DOI 10.1063/1.2828709 Kehr SC, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.256403 Kemp MC, 2011, IEEE T THZ SCI TECHN, V1, P282, DOI 10.1109/TTHZ.2011.2159647 Khalid A, 2014, J APPL PHYS, V115, DOI 10.1063/1.4868705 Kirley MP, 2015, IEEE T THZ SCI TECHN, V5, P1012, DOI 10.1109/TTHZ.2015.2468074 Kiwa T, 2003, OPT LETT, V28, P2058, DOI 10.1364/OL.28.002058 Koch M, 2001, NATO SCI SER II MATH, V27, P241 Koenig S, 2013, NAT PHOTONICS, V7, P977, DOI [10.1038/nphoton.2013.275, 10.1038/NPHOTON.2013.275] Kohler R, 2002, NATURE, V417, P156, DOI 10.1038/417156a Koppens FHL, 2014, NAT NANOTECHNOL, V9, P780, DOI [10.1038/nnano.2014.215, 10.1038/NNANO.2014.215] Kosarev A, 2010, SOLID STATE ELECTRON, V54, P417, DOI 10.1016/j.sse.2009.12.032 Kundu I, 2014, OPT EXPRESS, V22, P16595, DOI 10.1364/OE.22.016595 Kuznetsov SA, 2010, KEY ENG MATER, V437, P276, DOI 10.4028/www.scientific.net/KEM.437.276 Langevin Y, 2005, PAYLOAD MISSION DEFI LaRue JL, 2015, PHYS REV LETT, V115, DOI 10.1103/PhysRevLett.115.036103 Leitenstorfer A, 2014, NEW J PHYS, V16, DOI 10.1088/1367-2630/16/4/045016 Leitner DM, 2006, INT REV PHYS CHEM, V25, P553, DOI 10.1080/01442350600862117 Li LH, 2014, ELECTRON LETT, V50, P309, DOI 10.1049/el.2013.4035 Liu L, 2010, IEEE MICROW WIREL CO, V20, P504, DOI 10.1109/LMWC.2010.2055553 Liu SC, 2016, OPT EXPRESS, V24, P2728, DOI 10.1364/OE.24.002728 Lu X H, 2008, P SOC PHOTO-OPT INS, V7277 Luukanen A, 2003, APPL PHYS LETT, V82, P3970, DOI 10.1063/1.1579562 Mann C, 2009, P SOC PHOTO-OPT INS, V7311, P3970 Mickan S, 2004, PROC SPIE, V5277, P54, DOI 10.1117/12.530386 Mineo M, 2010, IEEE T ELECTRON DEV, V57, P3169, DOI 10.1109/TED.2010.2071876 Mittleman DM, 1996, IEEE J SEL TOP QUANT, V2, P679, DOI 10.1109/2944.571768 Mittleman DM, 1999, APPL PHYS B-LASERS O, V68, P1085, DOI 10.1007/s003400050750 Moon K, 2012, APPL PHYS LETT, V101, DOI 10.1063/1.4733475 Muller AS, 2010, REV ACCEL SCI TECH, V3, P165, DOI 10.1142/S1793626810000427 Muller R, 2015, J INFRARED MILLIM TE, V36, P654, DOI 10.1007/s10762-015-0163-7 Naftaly M, 2015, TERAHERTZ METROLOGY, P1 Nagai M, 2015, OPT EXPRESS, V23, P4641, DOI 10.1364/OE.23.004641 Nagatsuma T, 2012, OPT EXPRESS, V21, P477 Nagel M, 2002, APPL PHYS LETT, V80, P154, DOI 10.1063/1.1428619 Navarro-Cia M, 2015, J INFRARED MILLIM TE, V36, P542, DOI 10.1007/s10762-015-0157-5 Nielsen K, 2009, OPT EXPRESS, V17, P8592, DOI 10.1364/OE.17.008592 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 Nordquist CD, 2011, IEEE J SEL TOP QUANT, V17, P130, DOI 10.1109/JSTQE.2010.2049095 Oh SJ, 2012, J INFRARED MILLIM TE, V33, P74, DOI 10.1007/s10762-011-9847-9 Ojefors E, 2009, IEEE J SOLID-ST CIRC, V44, P1968, DOI 10.1109/JSSC.2009.2021911 Ortolani M, 2008, PHYS REV LETT, V97 Ozerov M, 2014, PHYS REV LETT, V113, DOI 10.1103/PhysRevLett.113.157205 Paoloni C, 2013, IEEE T ELECTRON DEV, V60, P1236, DOI 10.1109/TED.2013.2240686 Parrott EPJ, 2015, APPL SPECTROSC, V69, P1, DOI 10.1366/14-07707 Patrashin M, 2015, IEEE T ELECTRON DEV, V62, P1068, DOI 10.1109/TED.2015.2393358 Peiponen K. E., 2013, TERAHERTZ SPECTROSCO, V171 Peng K, 2015, NANO LETT, V15, P206, DOI 10.1021/nl5033843 Pickwell E, 2004, APPL PHYS LETT, V84, P2190, DOI 10.1063/1.1688448 Ponnampalam L, 2011, J LIGHTWAVE TECHNOL, V29, P2229, DOI 10.1109/JLT.2011.2158186 Pupeza I, 2007, OPT EXPRESS, V15, P4335, DOI 10.1364/OE.15.004335 Rauter P, 2015, LASER PHOTONICS REV, V9, P452, DOI 10.1002/lpor.201500095 Reid CB, 2011, PHYS MED BIOL, V56, P4333, DOI 10.1088/0031-9155/56/14/008 Reid J R, 2012, IEEE 12 TOP M SIL MO, P17 Rosch M, 2015, NAT PHOTONICS, V9, P42, DOI [10.1038/nphoton.2014.279, 10.1038/NPHOTON.2014.279] Rudd JV, 2000, PROC SPIE, V3934, P27, DOI 10.1117/12.386344 Rymanov V, 2015, PHOTONICS, V2, DOI 10.3390/photonics2041152 SANTOS Daisy Conceicao, 2014, THESIS Scherger B, 2011, APPL OPTICS, V50, P2256, DOI 10.1364/AO.50.002256 Schleicher JM, 2009, J APPL PHYS, V105, DOI 10.1063/1.3133093 Schumann S, 2012, OPT EXPRESS, V20, P19200, DOI 10.1364/OE.20.019200 Seeds AJ, 2015, J LIGHTWAVE TECHNOL, V33, P579, DOI 10.1109/JLT.2014.2355137 Sell A, 2008, OPT LETT, V33, P2767, DOI 10.1364/OL.33.002767 Shams H, 2015, IEEE PHOTONICS J, V7, DOI 10.1109/JPHOT.2015.2438437 Shams H, 2014, OPT EXPRESS, V22, P23465, DOI 10.1364/OE.22.023465 Shen YC, 2004, APPL PHYS LETT, V85, P164, DOI 10.1063/1.1768313 Simoens F., 2014, PHILOS T A, V372, P1 Simoens F, 2011, 36 INT C INFR MILL T, P1 Singh A, 2015, OPT EXPRESS, V23, P6656, DOI 10.1364/OE.23.006656 Sirtori C, 2013, NAT PHOTONICS, V7, P691, DOI [10.1038/NPHOTON.2013.208, 10.1038/nphoton.2013.208] SMITH PR, 1988, IEEE J QUANTUM ELECT, V24, P255, DOI 10.1109/3.121 Son JH, 2013, NANOTECHNOLOGY, V24, DOI 10.1088/0957-4484/24/21/214001 Swinyard B, 2013, SPIE SENSORS SYSTEMS Sy S, 2010, PHYS MED BIOL, V55, P7587, DOI 10.1088/0031-9155/55/24/013 Taylor ZD, 2015, IEEE T THZ SCI TECHN, V5, P184, DOI 10.1109/TTHZ.2015.2392628 Teppati V, 2013, CAMB RF MICROW ENG, P1, DOI 10.1017/CBO9781139567626 Tewari P, 2012, P SPIE, V8261 Thomas B., 2014, P 39 INT C INFR MILL, P1 Thumm M, 2014, KIT SCI REPORTS, V7693 Tonouchi M, 2007, NAT PHOTONICS, V1, P97, DOI 10.1038/nphoton.2007.3 Truong BCQ, 2015, IEEE T BIO-MED ENG, V62, P699, DOI 10.1109/TBME.2014.2364025 Turcinkova D, 2015, APPL PHYS LETT, V106, DOI 10.1063/1.4916653 Turner GM, 2002, J PHYS CHEM B, V106, P11716, DOI 10.1021/jp025844e van der Valk NCJ, 2002, APPL PHYS LETT, V81, P1558, DOI 10.1063/1.1503404 van Dijk F, 2014, IEEE PHOTONIC TECH L, V26, P965, DOI 10.1109/LPT.2014.2309353 Vicario C, 2014, PHYS REV LETT, V112, DOI 10.1103/PhysRevLett.112.213901 Vinh NQ, 2015, J CHEM PHYS, V142, DOI 10.1063/1.4918708 Vitiello MS, 2012, NAT PHOTONICS, V6, P525, DOI 10.1038/nphoton.2012.145 Vitiello MS, 2015, OPT EXPRESS, V23, P5167, DOI 10.1364/OE.23.005167 Vitiello MS, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms6884 Wade A, 2009, NAT PHOTONICS, V3, P41, DOI 10.1038/NPHOTON.2008.251 Wallace B., 2015, SPIE NEWSROOM, DOI [10.1117/2.1201503.005871, DOI 10.1117/2.1201503.005871] Wallace VP, 2004, BRIT J DERMATOL, V151, P424, DOI 10.1111/j.1365-2133.2004.06129.x Wang FH, 2015, OPTICA, V2, P944, DOI 10.1364/OPTICA.2.000944 Weightman P, 2012, PHYS BIOL, V9, DOI 10.1088/1478-3975/9/5/053001 Wienold M, 2014, OPT EXPRESS, V22, P3334, DOI 10.1364/OE.22.003334 Wilk R, 2007, C LAS EL BALT MD Williams BS, 2006, ELECTRON LETT, V42, P89, DOI 10.1049/el:20063921 Williams GP, 2006, REP PROG PHYS, V69, P301, DOI 10.1088/0034-4885/69/2/R01 Williams GP, 2008, NAT PHYS, V4, P356, DOI 10.1038/nphys958 Williams MRC, 2013, J PHYS CHEM B, V117, P10444, DOI 10.1021/jp406730a Williams R, 2013, PHYS MED BIOL, V58, P373, DOI 10.1088/0031-9155/58/2/373 Withayachumnankul W, 2008, J OPT SOC AM B, V25, P1059, DOI 10.1364/JOSAB.25.001059 Woerner M, 2013, NEW J PHYS, V15, DOI 10.1088/1367-2630/15/2/025039 Woodward RM, 2003, J INVEST DERMATOL, V120, P72, DOI 10.1046/j.1523-1747.2003.12013.x Wu X, OPT LETT, V39, P5403 Wu ZR, 2013, REV SCI INSTRUM, V84, DOI 10.1063/1.4790427 Xu J, 2003, PROC SPIE, V5268, P19, DOI 10.1117/12.518533 Yamashita M, 2011, OPT EXPRESS, V19, P10864, DOI 10.1364/OE.19.010864 Yan F, 2013, J INFRARED MILLIM TE, V34, P489, DOI 10.1007/s10762-013-0005-4 Yang SH, 2014, IEEE T THZ SCI TECHN, V4, P575, DOI 10.1109/TTHZ.2014.2342505 Yeh KL, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2734374 Zamora A, 2015, IEEE MTT S INT MICR Zhao JF, 2011, IEEE T ELECTRON DEV, V58, P1221, DOI 10.1109/TED.2011.2109723 Zheludev NI, 2012, NAT MATER, V11, P917, DOI [10.1038/NMAT3431, 10.1038/nmat3431] Zhou Y, 2010, PROG ELECTROMAGN RES, V105, P71, DOI 10.2528/PIER10041806 Zibik EA, 2009, NAT MATER, V8, P803, DOI [10.1038/nmat2511, 10.1038/NMAT2511] Dhillon, S. S. Vitiello, M. S. Linfield, E. H. Davies, A. G. Hoffmann, Matthias C. Booske, John Paoloni, Claudio Gensch, M. Weightman, P. Williams, G. P. Castro-Camus, E. Cumming, D. R. S. Simoens, F. Escorcia-Carranza, I. Grant, J. Lucyszyn, Stepan Kuwata-Gonokami, Makoto Konishi, Kuniaki Koch, Martin Schmuttenmaer, Charles A. Cocker, Tyler L. Huber, Rupert Markelz, A. G. Taylor, Z. D. Wallace, Vincent P. Zeitler, J. Axel Sibik, Juraj Korter, Timothy M. Ellison, B. Rea, S. Goldsmith, P. Cooper, Ken B. Appleby, Roger Pardo, D. Huggard, P. G. Krozer, V. Shams, Haymen Fice, Martyn Renaud, Cyril Seeds, Alwyn Stoehr, Andreas Naftaly, Mira Ridler, Nick Clarke, Roland Cunningham, John E. Johnston, Michael B. Huggard, Peter/U-2150-2019; Konishi, Kuniaki/AAN-3624-2020; Zeitler, J. Axel/B-4885-2008; Paoloni, Claudio/AAH-9824-2019; Hoffmann, Matthias C./N-1082-2019; Wallace, Vincent P/A-9320-2012; Johnston, Michael/B-9813-2008; Castro-Camus, Enrique/V-6861-2019; Krozer, Viktor/P-5623-2014; Hoffmann, Matthias C/B-3893-2009; PAOLONI, CLAUDIO/AAA-3211-2020; Gonokami, Makoto/F-3641-2012; Shams, Haymen/H-3754-2012; Ridler, Nick/AAN-9637-2020; Huber, Rupert/N-4126-2018 Konishi, Kuniaki/0000-0003-2389-9787; Zeitler, J. Axel/0000-0002-4958-0582; Hoffmann, Matthias C./0000-0002-3596-9853; Wallace, Vincent P/0000-0003-3814-5400; Johnston, Michael/0000-0002-0301-8033; Krozer, Viktor/0000-0002-2387-1947; Hoffmann, Matthias C/0000-0002-3596-9853; PAOLONI, CLAUDIO/0000-0002-0265-0862; Shams, Haymen/0000-0002-5333-6478; Huber, Rupert/0000-0001-6617-9283; Davies, Alexander/0000-0002-1987-4846; Seeds, Alwyn/0000-0002-5228-627X; Castro-Camus, Enrique/0000-0002-8218-9155; Cunningham, John/0000-0002-1805-9743; Naftaly, Mira/0000-0002-0671-822X; Cumming, David/0000-0002-7838-8362 Engineering and Physical Sciences Research CouncilUK Research & Innovation (UKRI)Engineering & Physical Sciences Research Council (EPSRC) [EP/P015883/1, EP/M00306X/1, EP/K023349/1, EP/M017095/1, EP/L026597/1, EP/J017671/1] Funding Source: researchfish; Natural Environment Research CouncilUK Research & Innovation (UKRI)NERC Natural Environment Research Council [NER/Z/S/2003/00642, NE/L012375/1, NER/Z/S/2000/01292] Funding Source: researchfish; Science and Technology Facilities CouncilUK Research & Innovation (UKRI)Science & Technology Facilities Council (STFC) [ST/P002056/1] Funding Source: researchfish; Direct For Biological SciencesNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Biological InfrastructureNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Molecular and Cellular BioscienceNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1616529] Funding Source: National Science Foundation 566 30 462 Iop publishing ltd Bristol 1361-6463
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Terahertz Response and Colossal Kerr Rotation from the Surface States of the Topological Insulator Bi2Se3 - Aguilar, R. V.; Stier, A. V.; Liu, W.; Bilbro, L. S.; George, D. K.; Bansal, N.; Wu, L.; Cerne, J.; Markelz, A. G.; Oh, S.; Armitage, N. P. (Physical Review Letters, 2012)
We report the THz response of thin films of the topological insulator Bi2Se3. At low frequencies, transport is essentially thickness independent showing the dominant contribution of the surface electrons. Despite their extended exposure to ambient conditions, these surfaces exhibit robust properties including narrow, almost thickness-independent Drude peaks, and an unprecedentedly large polarization rotation of linearly polarized light reflected in an applied magnetic field. This Kerr rotation can be as large as 65 degrees and can be explained by a cyclotron resonance effect of the surface states.
ISI Document Delivery No.: 896NY Times Cited: 164 Cited Reference Count: 35 Cited References: Akhmerov AR, 2009, PHYS REV LETT, V102, DOI 10.1103/PhysRevLett.102.216404 Alpichshev Z, 2010, PHYS REV LETT, V104, DOI 10.1103/PhysRevLett.104.016401 Analytis JG, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.205407 Bansal N., ARXIV11045709 Benia HM, 2011, PHYS REV LETT, V107, DOI 10.1103/PhysRevLett.107.177602 Bianchi M, 2010, NAT COMMUN, V1, DOI 10.1038/ncomms1131 Butch NP, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.241301 Chen J, 2011, PHYS REV B, V83, DOI 10.1103/PhysRevB.83.241304 Chen YL, 2009, SCIENCE, V325, P178, DOI 10.1126/science.1173034 Essin AM, 2009, PHYS REV LETT, V102, DOI 10.1103/PhysRevLett.102.146805 Eto K, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.195309 Fu L, 2007, PHYS REV B, V76, DOI 10.1103/PhysRevB.76.045302 Fu L, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.096407 Hsieh D, 2008, NATURE, V452, P970, DOI 10.1038/nature06843 Hsieh D, 2009, NATURE, V460, P1101, DOI 10.1038/nature08234 Jenkins GS, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.125120 King PDC, 2011, PHYS REV LETT, V107, DOI 10.1103/PhysRevLett.107.096802 LaForge AD, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.125120 Lan YP, 2011, PHYS REV B, V83, DOI 10.1103/PhysRevB.83.205109 Maciejko J, 2010, PHYS REV LETT, V105, DOI 10.1103/PhysRevLett.105.166803 Moore JE, 2007, PHYS REV B, V75, DOI 10.1103/PhysRevB.75.121306 Qi XL, 2008, PHYS REV B, V78, DOI 10.1103/PhysRevB.78.195424 Qu DX, 2010, SCIENCE, V329, P821, DOI 10.1126/science.1189792 Roushan P, 2009, NATURE, V460, P1106, DOI 10.1038/nature08308 Roy R, 2009, PHYS REV B, V79, DOI 10.1103/PhysRevB.79.195322 Steinberg H, 2011, PHYS REV B, V84, DOI 10.1103/PhysRevB.84.233101 Sushkov AB, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.125110 THOULESS DJ, 1982, PHYS REV LETT, V49, P405, DOI 10.1103/PhysRevLett.49.405 Tkachov G, 2011, PHYS REV B, V84, DOI 10.1103/PhysRevB.84.035405 Tse WK, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.161104 Tse WK, 2010, PHYS REV LETT, V105, DOI 10.1103/PhysRevLett.105.057401 VONKLITZING K, 1980, PHYS REV LETT, V45, P494, DOI 10.1103/physrevlett.45.494 Xia Y, 2009, NAT PHYS, V5, P398, DOI 10.1038/NPHYS1274 Xiong J., PHYSICA A E IN PRESS Zhang XA, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.245107 Aguilar, R. Valdes Stier, A. V. Liu, W. Bilbro, L. S. George, D. K. Bansal, N. Wu, L. Cerne, J. Markelz, A. G. Oh, S. Armitage, N. P. George, Deepu/J-9882-2014; Aguilar, Rolando Valdes/A-6637-2012; Liu, Wei/H-5999-2012; Wu, Liang/C-8715-2015 George, Deepu/0000-0003-0021-0705; Aguilar, Rolando Valdes/0000-0002-4321-4792; Wu, Liang/0000-0003-1696-7809; Markelz, Andrea/0000-0003-0443-4319 "Institute for Quantum Matter" DOE [DE-FG02-08ER46544]; Gordon and Betty Moore FoundationGordon and Betty Moore Foundation; NSFNational Science Foundation (NSF) [MRI-R2 0959989, DMR-1006078, DMR-0845464]; IAMDN of Rutgers University; ONROffice of Naval Research [N000140910749]; Division Of Materials ResearchNational Science Foundation (NSF)NSF - Directorate for Mathematical & Physical Sciences (MPS) [0845464] Funding Source: National Science Foundation The authors would like to thank H. D. Drew, J. Hancock, Z. Hao, G. S. Jenkins, A. Kuzmenko, A. MacDonald, N. A. Mecholsky, A. J. Pearson, O. Tchernyshyov, W-K. Tse, and Y. Wan for helpful discussions and/or correspondences. Support for the measurements at JHU was provided under the auspices of the "Institute for Quantum Matter" DOE DE-FG02-08ER46544 and the Gordon and Betty Moore Foundation. The work at UB was supported by NSF MRI-R2 0959989 and NSF DMR-1006078. The work at Rutgers was supported by IAMDN of Rutgers University, NSF DMR-0845464 and ONR N000140910749. 166 3 157 Amer physical soc College pk
Keywords: bi2te3; Physics

Ultrafast Carriers Dynamics in GaSb/Mn Random Alloys - Ye, S.; Knab, J.; Chen, J.-Y.; Wang, S.; Cheon, M.; Luo, H.; Markelz, A. G. (Proceedings of the 28th International Conference on the Physics of Semiconductors, 2006)

Direct measurements of optical phonons in SrTiO3 nanosystems - Wolpert, D; Korolev, K; Sachs, S; Knab, J; Cox, W; Cerne, J; Markelz, A.G; Zhao, T; Ramesh, R; Moeckly, B.H (Physica E: Low-dimensional Systems and Nanostructures, 2003)
We use terahertz time domain spectroscopy to examine finite size effects on the optical phonon modes in SrTiO3 thin films. In temperature-dependent measurements we find a near absence of mode softening in the TO1 phonon frequency. Furthermore we see an increase in the soft mode frequency with reduced thickness. Both of these results correlate well with the reduced dielectric response observed for nanoscale ferroelectric systems.
Keywords: Ferroelectrics; Finite size; Mode softening; phonons; Strontium titanate; Terahertz

Finite size effects in ferroelectric nanosystems: Absence of mode softening - D. Wolpert; W. Cox; J. Cerne; A. Markelz; T. Zhao; R. Ramesh (2003 Nanotechnology Conference and Trade Show - Nanotech, 2003)
We present measurements of the mode softening behavior for PbZr 0.5Ti0.5O3 (PZT(50)) thin films using terahertz time domain spectroscopy (TTDS). The films were grown using pulsed laser deposition (PLD) techniques on silicon substrates to study how reduced size affects the mode softening behavior. At room temperature two modes are observed at 1.1 THz (37 cm-1) and at 2.3 THz (77 cm-1). As the temperature is increased toward Tc we do not see strong mode softening, but rather a spectral weight transfer from the high frequency mode to the low frequency mode. This absence of mode softening is more dramatic than that reported by other investigators[1]. We will discuss the possible sources for this discrepancy. These results suggest a change in lattice dynamics for nanoscale ferroelectric films that may be highly dependent on the sample preparation technique.
cited By 0
Keywords: Ferroelectric materials; Fourier Transform Infrared Spectroscopy; Frequency ranges; Lead compounds; Mode softening; nanostructured materials; Natural frequencies; Optical modes; Permittivity; phase transitions; phonons; Routers; Thermal effects

Protein flexibility and conformational state: A comparison of collective vibrational modes of wild-type and D96N bacteriorhodopsin - Whitmire, S. E.; Wolpert, D.; Markelz, A. G.; Hillebrecht, J. R.; Galan, J.; Birge, R. R. (Biophysical Journal, 2003)
Far infrared ( FIR) spectral measurements of wild-type (WT) and D96N mutant bacteriorhodopsin thin films have been carried out using terahertz time domain spectroscopy as a function of hydration, temperature, and conformational state. The results are compared to calculated spectra generated via normal mode analyses using CHARMM. We find that the FIR absorbance is slowly increasing with frequency and without strong narrow features over the range of 2-60 cm(-1) and up to a resolution of 0.17 cm(-1). The broad absorption shifts in frequency with decreasing temperature as expected with a strongly anharmonic potential and in agreement with neutron inelastic scattering results. Decreasing hydration shifts the absorption to higher frequencies, possibly resulting from decreased coupling mediated by the interior water molecules. Ground-state FIR absorbances have nearly identical frequency dependence, with the mutant having less optical density than the WT. In the M state, the FIR absorbance of the WT increases whereas there is no change for D96N. These results represent the first measurement of FIR absorbance change as a function of conformational state.
ISI Document Delivery No.: 705ZZ Times Cited: 117 Cited Reference Count: 55 Cited References: AUSTIN RH, 1975, BIOCHEMISTRY-US, V14, P5355, DOI 10.1021/bi00695a021 Birge RR, 1996, J PHYS CHEM-US, V100, P9990, DOI 10.1021/jp953669e BOUSCHE O, 1992, PHOTOCHEM PHOTOBIOL, V56, P1085, DOI 10.1111/j.1751-1097.1992.tb09732.x BROOKS BR, 1983, J COMPUT CHEM, V4, P187, DOI 10.1002/jcc.540040211 BROOKS BR, 1995, J COMPUT CHEM, V16, P1522, DOI 10.1002/jcc.540161209 Brooks CL, 1988, PROTEINS THEORETICAL Brucherseifer M, 2000, APPL PHYS LETT, V77, P4049, DOI 10.1063/1.1332415 Chen Q, 2001, J OPT SOC AM B, V18, P823, DOI 10.1364/JOSAB.18.000823 DENCHER NA, 1989, P NATL ACAD SCI USA, V86, P7876, DOI 10.1073/pnas.86.20.7876 Der A, 2001, BIOCHEMISTRY-MOSCOW+, V66, P1234, DOI 10.1023/A:1013179101782 Diehl M, 1997, BIOPHYS J, V73, P2726, DOI 10.1016/S0006-3495(97)78301-2 DOSTER W, 1989, NATURE, V337, P754, DOI 10.1038/337754a0 FERRAND M, 1993, P NATL ACAD SCI USA, V90, P9668, DOI 10.1073/pnas.90.20.9668 GENZEL L, 1984, SPECTROSCOPY BIOL MO, P609 GRISCHKOWSKY D, 1991, OSA PROC, V9, P9 Guilbert C, 1996, CHEM PHYS, V204, P327, DOI 10.1016/0301-0104(95)00293-6 Han PY, 2000, OPT LETT, V25, P242, DOI 10.1364/OL.25.000242 Hinsen K, 1998, PROTEINS, V33, P417, DOI 10.1002/(SICI)1097-0134(19981115)33:3<417::AID-PROT10>3.0.CO;2-8 JANEZIC D, 1995, J COMPUT CHEM, V16, P1543, DOI 10.1002/jcc.540161210 Kusnetzow A, 1999, BIOPHYS J, V76, P2370, DOI 10.1016/S0006-3495(99)77394-7 Lanyi JK, 1999, INT REV CYTOL, V187, P161, DOI 10.1016/S0074-7696(08)62418-3 Lanyi JK, 2001, TRENDS BIOTECHNOL, V19, P140, DOI 10.1016/S0167-7799(01)01576-1 LINDSAY SM, 1988, BIOPOLYMERS, V27, P1015, DOI 10.1002/bip.360270610 Lisy V, 1997, J BIOMOL STRUCT DYN, V14, P517, DOI 10.1080/07391102.1997.10508150 LONGBOTTOM C, 2002, POTENTIAL USES TERAH Luecke H, 1999, SCIENCE, V286, P255, DOI 10.1126/science.286.5438.255 Luecke H, 1999, J MOL BIOL, V291, P899, DOI 10.1006/jmbi.1999.3027 MacKerell AD, 1998, J PHYS CHEM B, V102, P3586, DOI 10.1021/jp973084f Markelz AG, 2000, CHEM PHYS LETT, V320, P42, DOI 10.1016/S0009-2614(00)00227-X MCINTOSH AR, 1991, BIOPHYS J, V60, P1, DOI 10.1016/S0006-3495(91)82025-2 MOUAWAD L, 1993, BIOPOLYMERS, V33, P599, DOI 10.1002/bip.360330409 Mouawad L, 1996, J MOL BIOL, V258, P393, DOI 10.1006/jmbi.1996.0257 Nagel M, 2002, APPL PHYS LETT, V80, P154, DOI 10.1063/1.1428619 Oesterhelt D, 1974, Methods Enzymol, V31, P667 Palmo K, 1998, J COMPUT CHEM, V19, P754, DOI 10.1002/(SICI)1096-987X(199805)19:7<754::AID-JCC6>3.0.CO;2-P PERAHIA D, 1995, COMPUT CHEM, V19, P241, DOI 10.1016/0097-8485(95)00011-G Person W.B., 1982, VIBRATIONAL INTENSIT Polavarapu P. L., 1998, VIBRATIONAL SPECTRA POWELL JW, 1991, J MOL STRUCT, V247, P107, DOI 10.1016/0022-2860(91)87067-R POWELL JW, 1987, PHYS REV A, V35, P3929, DOI 10.1103/PhysRevA.35.3929 Ren L, 2001, BIOCHEMISTRY-US, V40, P13906, DOI 10.1021/bi0116487 ROITBERG A, 1995, SCIENCE, V268, P1319, DOI 10.1126/science.7539156 Sass HJ, 1997, EMBO J, V16, P1484, DOI 10.1093/emboj/16.7.1484 Stuart JA, 1996, BIOMEMBR A&B, V2, P33 Urabe H, 1998, BIOPHYS J, V74, P1533, DOI 10.1016/S0006-3495(98)77865-8 VARO G, 1983, BIOPHYS J, V43, P47, DOI 10.1016/S0006-3495(83)84322-7 Walther M, 2000, CHEM PHYS LETT, V332, P389, DOI 10.1016/S0009-2614(00)01271-9 WEIDLICH T, 1990, BIOPOLYMERS, V30, P477, DOI 10.1002/bip.360300324 WEIDLICH T, 1990, J BIOMOL STRUCT DYN, V8, P139, DOI 10.1080/07391102.1990.10507795 WEIDLICH T, 1987, BIOPOLYMERS, V26, P439, DOI 10.1002/bip.360260310 WEIDLICH T, 1988, J PHYS CHEM-US, V92, P6475 WITTLIN A, 1986, PHYS REV A, V34, P493, DOI 10.1103/PhysRevA.34.493 Woolard DL, 1997, J APPL TOXICOL, V17, P243, DOI 10.1002/(SICI)1099-1263(199707)17:4<243::AID-JAT436>3.0.CO;2-6 Xie AH, 2002, PHYS REV LETT, V88, DOI 10.1103/PhysRevLett.88.018102 Zaccai G, 2000, SCIENCE, V288, P1604, DOI 10.1126/science.288.5471.1604 Whitmire, SE Wolpert, D Markelz, AG Hillebrecht, JR Galan, J Birge, RR Markelz, Andrea/0000-0003-0443-4319 NATIONAL INSTITUTE OF GENERAL MEDICAL SCIENCESUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548] Funding Source: NIH RePORTER; NIGMS NIH HHSUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R01 GM034548, R01 GM034548-15] Funding Source: Medline 122 3 31 Cell press Cambridge 1542-0086
Keywords: angstrom resolution; Biophysics; dna; films; frequency; harmonic-analysis; inelastic neutron-scattering; large systems; mixed basis; normal-modes; purple membranes; structural-changes; transform infrared-spectroscopy

Terahertz Applications to Biomolecular Sensing - Markelz, A. G.; Whitmire, S. E. (International Journal of High Speed Electronics and Systems, 2003)

Terahertz applications to biomolecular sensing - Markelz, Andrea G; Whitmire, Scott E (International Journal of High Speed Electronics and Systems, 2003)

Ultrafast THz spectroscopy of photoactive biomolecules - Chen, J.-Y.; Whitmire, S. E.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Ultrafast Phenomena in Semiconductors VII, 2003)

THz time domain spectroscopy of biomolecular conformational modes - Markelz, Andrea; Whitmire, Scott; Hillebrecht, Jay; Birge, Robert (Physics in Medicine & Biology, 2002)

Terahertz Time domain spectroscopy of the M intermediate state of Bacteriorhodopsin - Whitmire, S.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Proceedings of the 26th International Conference on Infrared and Millimeter Waves, 2001)

Third Harmonic Generation in a Gaas/Algaas Superlattice in the Bloch Oscillator Regime - Wanke, M. C.; Markelz, A. G.; Unterrainer, K.; Allen, S. J.; Bhatt, R. (Hot Carriers in Semiconductors, 1996)

Undressing a collective intersubband excitation in a quantum well - Craig, K.; Galdrikian, B.; Heyman, J. N.; Markelz, A. G.; Williams, J. B.; Sherwin, M. S.; Campman, K.; Hopkins, P. F.; Gossard, A. C. (Physical Review Letters, 1996)
We have experimentally measured the 1-2 intersubband absorption in a single 40 nm wide modulation-doped Al0.3Ga0.7As/GaAs square quantum well as a function of frequency, intensity, and charge density. The low-intensity depolarization-shifted absorption occurs near 80 cm(-1) (10 meV or 2.4 THz), nearly 30% higher than the intersubband spacing. At higher intensities, the absorption peak shifts to lower frequencies. Our data are in good agreement with a theory proposed by Zaluzny, which attributes the redshift to a reduction in the depolarization shift as the excited subband becomes populated.
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 78

Third harmonic generation in a GaAs/AlGaAs Superlattice in the Bloch Oscillator Regime - Wanke, M. C.; Markelz, A.G.; Unterrainer, K.; Allen, S. J.; Bhatt, R. (Proceedings of the International Conference on Hot Carriers in Seminconductors, 1995)

Site-selective oxygen-isotope substitution in YBa2Cu3O7−δ - Morris, D. E.; Markelz, A. G.; Wei, J. Y. T.; Huitgren, C. T.; Nickel, J. H.; Hamilton, J. C.; McCarty, K. F. (Physical Review B, 1991)
We report selective substitution of oxygen-18 and oxygen-16 isotopes into the inequivalent oxygen lattice sites in YBa2Cu3O7−δ. The technique involves gas-phase diffusion and exploits the site dependence of diffusion rates. The CuO2-plane [O(2),O(3)] sites of YBa2Cu3O7−δ can be filled with 18O while the apical [O(4)] and CuO-chain sites [O(1)] contain 16O (the opposite distribution can also be made). The site-selective isotope occupation has been confirmed by Raman spectroscopy. Our method will permit experiments to determine the contributions of the different oxygen sites to the isotope effect, in order to locate the pairing interaction within the unit cell.

8 NEW HIGH-TEMPERATURE SUPERCONDUCTORS WITH THE 1-2-4 STRUCTURE - Morris, D. E.; Nickel, J. H.; Wei, J. Y. T.; Asmar, N. G.; Scott, J. S.; Scheven, U. M.; Hultgren, C. T.; Markelz, A. G.; Post, J. E.; Heaney, P. J.; Veblen, D. R.; Hazen, R. M. (Physical Review B, 1989)
Scheven, Ulrich/D-7582-2013 Markelz, Andrea/0000-0003-0443-4319; Scheven, Ulrich/0000-0001-8111-0081 B 241

OXYGEN CONCENTRATION EFFECT ON TC OF THE BI-CA-SR-CU-O SUPERCONDUCTOR - Morris, D. E.; Hultgren, C. T.; Markelz, A. M.; Wei, J. Y. T.; Asmar, N. G.; Nickel, J. H. (Physical Review B, 1989)
A 155

SMALL OXYGEN ISOTOPE SHIFT IN YBA2CU3O7 - Morris, D. E.; Kuroda, R. M.; Markelz, A. G.; Nickel, J. H.; Wei, J. Y. T. (Physical Review B, 1988)
Markelz, Andrea/0000-0003-0443-4319 B 74

SPECIFIC-HEAT MEASUREMENTS ON SUPERCONDUCTING BI-CA-SR-CU AND TL-CA-BA-CU OXIDES - ABSENCE OF A LINEAR TERM IN THE SPECIFIC-HEAT OF BI-CA-SR-CU OXIDES - Fisher, R. A.; Kim, S.; Lacy, S. E.; Phillips, N. E.; Morris, D. E.; Markelz, A. G.; Wei, J. Y. T.; Ginley, D. S. (Physical Review B, 1988)
Fisher, Robert Anthony/H-6779-2019 Markelz, Andrea/0000-0003-0443-4319 B 68